Activated carbon from pencil peel waste for effective removal of cationic crystal violet dye from aqueous solutions - Dilip D. Anuse; Suryakant A. Patil; Ashwini A. Chorumale; Akanksha G. Kolekar; Prachi P. Bote; Laxman S. Walekar; Samadhan P. Pawar (Results in Chemistry)
In this investigation, the pencil peel (PP) is utilized as a scavenger for adsorptive removal of crystal violet (CV) dye. Pencil peel activated carbon (PPAC) is produced through a straightforward physical activation method by annealing pencil peel in a muffle furnace at 300 °C. The prepared PPAC shows the mesoporous nature having specific surface area of 217.44 m2 g−1. The highest uptake of CV dye was observed at equilibrium as working solution pH-8.0, CV dye concentration-100 mg L-1, the PPAC dosage-0.25 g at 200 rpm speed. The observed experimental results align with the Freundlich adsorption isotherm model, suggesting of multilayer adsorption. The kinetic study attributes the uptake rate adheres to the pseudo-second-order kinetic rate model (regression coefficient, R2 = 0.99).